1997
DOI: 10.1002/(sici)1097-4628(19970815)65:7<1395::aid-app18>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Cell distributions in and sound absorption characteristics of flexible polyurethane foams

Abstract: ABSTRACT:In this article, the two-dimensional distributions of cells from the cross section of some flexible polyurethane foams were cleared, and the three-dimensional distributions of cells based on Saltykov's theory were estimated further. As a result, it was found that a mean of the two-dimensional distributions of cells was a good linear relation with a mean of the three-dimensional distributions of cells, and it was confirmed that cell structure of the foams which should have been analyzed in the threedim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this work, we use a stereological analysis, the Saltykov method, to reconstruct the three‐dimensional bubble size distribution from the two‐dimensional pore size distribution [19]. This method has been applied successfully in studying titanium foam [20] and polyurethane foam [21].…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we use a stereological analysis, the Saltykov method, to reconstruct the three‐dimensional bubble size distribution from the two‐dimensional pore size distribution [19]. This method has been applied successfully in studying titanium foam [20] and polyurethane foam [21].…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the studies on PU foam focus on the influence of pore sizes, pore structures, and material intrinsic parameters on the acoustic properties and sound waves transmission mechanism of materials. [13][14][15][16][17] Adachi et al 18 investigated the two-dimensional distributions of cells from the cross section and three-dimensional distributions of cells of polyester-based flexible PU foams. Their analysis showed that the cell number, cell distribution, and cell diameter all have important effects on the sound absorption properties of PU foams.…”
Section: Introductionmentioning
confidence: 99%
“…Although PU foam has been applied in the field of acoustic materials, the inhomogeneous size and distribution of its internal pores limit its application fields. 18,21,31,32 However, metallic hollow spheres developed in recent years are a relative controllable cavity material with size and distribution, which can solve the above shortcomings of PU foam. In recent years, metallic hollow spheres have been widely reported in the field of metal foams, [33][34][35][36][37][38] while there are few reports about hollow metal spheres/polymer composites.…”
Section: Introductionmentioning
confidence: 99%